REFORMASIKELEMBAGAANPESANTREN SEBAGAILEMBAGA PENDIDIKAN BERBASIS MASYARAKAT DIINDONESIA - Murdianto Murdianto (Universitas Islam Negeri (UIN) Mataram, 2017)
Pesantren is a community-based education institution that has lived and developed in Indonesia before independence. The pattern of community-based education developed in pesantren, in addition to being born out of the community’s own initiative, is also supported by state policy through the National Education System Act no. 20 of 2003, reinforced by Government Regulation No. 66 of 2010 concerning Amendment to Government Regulation No. 17 of 2010 on Management and Implementation of Education. The existence of pesantren as a communitybased educational institution not only manages the Salafiyah model education which focuses on religious studies by studying the yellow book, but also the modern education model that integrates the study of religion, sciences, and science and technology. While institutional reform of pesantren is a mandate of the law as a form of communitybased education, because the involvement of the community ranging from planning, establishing, managing, menumbuhkembangkan and evaluate the educational institutions in Indonesia, specially pesantren.